Fabrication and characterization of magnetic FePt nanoparticles prepared by extraction–pyrolysis method - Serga, Vera E.; Maiorov, Mikhail M.; Cvetkovs, Antons; Krūmiņa, Aija P.; Popov, Anatoli I. (Lietuvos Mokslu Akademijos, 2018)
In the present work, possibilities of the extraction–pyrolysis method (EPM) to produce FePt nanoparticles with the face-centered tetragonal (fct) phase were studied. A mixture of fine-disperse powder of carbonyl iron and n-trioctylam-monium hexachloroplatinate [(С8Н17)3NH]2PtCl6 solution in toluene, preliminary produced by the solvent extraction method, is used as a precursor. Precursors with a different molar ratio of metals were used. The performed investigations show that as a result of pyrolysis in the air (Tpyr = 600°C, tanneal = 30 min), a FePt alloy with the fct phase is produced. Moreover, such phases as FePt3 and/or Fe3Pt with the cubic structure may be also present in the final products. The phase composition of the produced samples depends on the Fe:Pt molar ratio in the precursor. An increase of the fct phase part with the growth of the iron content from 40 to 60 mol% is observed. Also, with the Fe80%Pt20% molar ratio of the metals in the precursor, only the ordered fct phase along with a small amount of hematite and iron chloride exists in the produced sample. Magnetic measurements confirm the fct-FePt phase formation in all produced samples and evidence that the coercivity exceeds the value (3 kOe) at the 50 mol% Fe concentration in the precursor and significantly decreases with increasing the Fe concentration to 80 mol%.
We are grateful to Prof. E. Kotomin for useful discussions. The research leading to these results has received funding from the ERAF (2017) Project, while A. I. Popov thanks IMIS-2 for the funding support.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Extraction–pyrolysis method; Fe/Pt composition; FePt alloy; High magnetic coercivity